Model Integrasi Green Productivity dalam Optimalisasi Pengolahan Limbah dan Produktivitas Berkelanjutan Industri UMKM Tahu Samarinda - Ida Rosanti; Andrew Stefano; Purbawati Purbawati (Fakultas Teknik Universitas Tulang Bawang, 2026)
The tofu Micro, Small, and Medium Enterprise (MSME) sector constitutes a vital agro-industrial component that significantly contributes to food security and local economic development. Nevertheless, its sustainability remains constrained by inefficient resource utilization and suboptimal waste management practices. This study aimed to develop an integrated Green Productivity–Fishbone Diagram model to optimize waste management while enhancing sustainable productivity in tofu MSMEs in Samarinda, Indonesia. A descriptive quantitative approach was employed through field observations, structured interviews, documentation, and direct measurements. Productivity performance was assessed using Key Performance Indicators (KPIs), whereas environmental performance was evaluated through the Environmental Performance Indicator (EPI). The findings revealed a production capacity of 1,650 units per month, a financial productivity index of 1.1165, and an improvement in productivity from 104.9% to 107.4%. A multi-stage filtration system utilizing coconut shell activated carbon effectively reduced COD concentrations from 1,449.162 to 213.945 mg/L and BOD from 136.79 to 135.50 mg/L, achieving removal efficiencies of 85.24% and 0.95%, respectively, while increasing pH from 3.68 to 6.59, thereby complying with the applicable wastewater quality standards. The proposed model substantially improves resource efficiency, strengthens environmental performance, and supports the implementation of circular economy principles for sustainable tofu MSME development. Keywords: Activated Carbon ; Environmental; Fishbone Diagram, Green Productivity, Sustainable productivity